MOTIVASI DAN AKTIVITAS BELAJAR BAHASA INGGRIS MAHASISWAKEPERAWATAN TINGKAT IV DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPEWORDSQUARE - Tinambunan, Tedty Rohaya; Ginting, Sulastri Br; Silaban, Roikestina (Jurnal Penelitian Keperawatan Medik, 2023)
Using a cooperative learning model of the Word Square variety, the study sought to enhance the English language learning activities and motivation of nursing students at the Health Institute of DELI HUSADA Deli Tua Deli Serdang. The study took place in September and August of 2023. Thirty DELI HUSADA Deli Tua Class B Nursing Students, sixteen of whom were female and fourteen of whom were boy, comprised the samples for the academic year 2023–2024. The parameters of measurement were student motivation and learning activities. The results showed that student motivation had increased. Prior to the action, the average student motivation was 2.92 (medium category), but in the first cycle, it increased to 4.21 (high category). In the second cycle, students' motivation rose by an average of 4.56 points (high category). The average percentage of student learning activities increased in the first cycle category, where there was a sufficient amount of 669.95%. The average percentage for both categories in the second cycle was 84.45%.The study's findings suggest that using Word Type Square's Cooperative Learning Model to teach students can boost their enthusiasm and engagement in the classroom. in English classes at Class B of Nursing Students DELI HUSADA Deli Tua in Academic Year 2023/2024.